A systematic review and meta‐analysis on complications of transanal total mesorectal excision. (11th July 2021) - An, Yongbo; Roodbeen, Sapho X.; Talboom, Kevin; Tanis, Pieter J.; Bemelman, Willem A.; Hompes, Roel
Abstract: Aim: Transanal total mesorectal excision (TaTME) is a surgical approach for treating mid to low rectal cancer as well as other colorectal diseases. Since the procedure is difficult to master, perioperative complications of TaTME should be examined precisely, especially during the early implementation phase of this procedure. The primary aim of this review was to determine a pooled morbidity and anastomotic leakage (AL) rate after TaTME surgery, and the secondary aim was to show the completeness of reporting of complications among the included studies, as well as the correlation between completeness and reported incidence of complications. Method: A systematic review of literature was conducted using Medline, Embase and Cochrane databases, searching for observational studies reporting on complications after TaTME. Studies published between 1 January 2010 and 15 October 2019 were included. Meta‐analysis on the proportion of morbidity, AL and intraoperative complications was performed. Results: Forty‐one studies (2446 TaTME cases), consisting of 27 noncomparative studies and 14 comparative studies, were included, after screening 1711 possible studies. The pooled rates of overall morbidity and AL were 30.0% (95% CI 26.4%–34.0%) and 6.8% (95% CI 5.2%–8.9%), respectively. Subgroup analysis showed that the morbidity rate in studies that reported 30‐day results (35.5%; 95% CI 31.8%–39.4%) was significantly higher than the rate in studies that did not define the follow‐up length for complications (23.4%; 95% CI 17.8%–30.1%; p = 0.003). The rates of intraoperative urethral injury, rectal injury, vaginal injury and bladder injury were 0.3% (95% CI 0.1%–1.7%), 0.4% (95% CI 0.1%–2.2%), 0.3% (95% CI 0.1%–0.8%) and 0.3% (95% CI 0.1%–1.7%), respectively. Conclusion: This meta‐analysis shows that pooled perioperative complication rates were within acceptable ranges. However, the significant difference in overall morbidity rate between the studies with 30‐day results and the studies without a specified follow‐up time, indicates a large under‐reporting of complications in many studies.